A revisited study of Cepheids in open clusters in the Gaia era - Medina, Gustavo E.; Lemasle, Bertrand; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT. In this paper, we revisit the problem of identifying bona fide cluster Cepheids by performing an all-sky search for Cepheids associated